Ethical Leadership as Antecedent of Job Satisfaction, Affective Organizational Commitment and Intention to Stay Among Volunteers of Non-profit Organizations - Benevene, Paula; Dal Corso, Laura; De Carlo, Alessandro; Falco, Alessandra; Carluccio, Francesca; Vecina, Maria Luisa (Frontiers in Psychology, 2018)
The aim of this paper is to investigate among a group of non-profit organizations: a) the effect of ethical leadership on volunteers’ satisfaction, affective organizational commitment and intention to stay in the same organization; b) the role played by job satisfaction as a mediator in the relationship between ethical leadership and volunteers’ intentions to stay in the same organization, as well as between ethical leadership and affective commitment. An anonymous questionnaire was individually administered to 198 Italian volunteers of different non-profit organizations. The questionnaire contained the Ethical Leadership Scale, the Volunteers Satisfaction Index, the Affective organization Scale, as well as questions regarding the participants’ age, sex, type of work, level of education, length of their volunteer works, intention to volunteer in the following months in the same organization. The construct as well the effects of EL on volunteers is approached in light of the Social Exchange Theory and the Social Learning Theory. Structural equation models were used to test hypothesized relationships. The results confirm the role of mediation of volunteer satisfaction in the relationships between the variables studied. In particular, ethical leadership was found to be positively associated both with volunteers’ intention of staying and with their affective commitment. In the first case this relationship is fully explained by the mediation of the volunteers’ satisfaction, while the latter is explained by both direct and indirect factors. To the authors’ knowledge, this the first attempt to understand the role played by ethical leadership on volunteers’ behavior and, more in general, in the management of non-profit organizations. Findings are relevant both for practitioners and managers of non-profit organization, since they suggest the relevance of the perception of ethical leadership by volunteers, as well as for scholars, since they further deepen the knowledge on EL and its effects on the followers. Limits of the study: the questionnaire was administered only among a group of non-statistical sample of volunteers. Furthermore, the study reached only volunteers from Italian non-profit organization.